If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8c+14=-6c+12
We move all terms to the left:
8c+14-(-6c+12)=0
We get rid of parentheses
8c+6c-12+14=0
We add all the numbers together, and all the variables
14c+2=0
We move all terms containing c to the left, all other terms to the right
14c=-2
c=-2/14
c=-1/7
| (2x+50)=3x | | -4.3(6.3x+-4.18)=58.56 | | 2x=1680 | | 18x-5-7x-13=25 | | 3x+-4=-1 | | 3(y+7)=4y-6 | | 0.75q^2=108 | | (X-2)=6x | | -10(8x-4)=-4(6+12x) | | -9(-9x-8)=-8x-17 | | 8x-32=56+6x | | 8q^2-23q-3=0 | | -9(-9x-8=-8x-17 | | -21=2x-(7-13) | | 7x-24+5x+14=13 | | 3+8x=3(2x)- | | 5n=100* | | 5(7k-3)=-8k-15 | | x2 –4x–5=0 | | 8j-6=-30 | | -67+h=35 | | n/5-3=-10 | | z^2-23z-24=0 | | 12u-5(4u+5)=50 | | 10x+12=5x+57 | | 5(2e+2e+1=) | | 4x-26+3x+4=5 | | 3p^2+5p-8=0 | | v^2-18+17=0 | | 2u^2+19u-10=0 | | y=990-60 | | -3x-4=5x-28 |